Unveiling the Pharmacognostic Potential of Peucedanum ostruthium (L.) W.D.J. Koch: A Comparative Study of Rhizome and Leaf Essential Oils - Cristina Danna; Andrea Mainetti; Souda Belaid; Erminia La Camera; Domenico Trombetta; Laura Cornara; Antonella Smeriglio (Plants, 2025)
Peucedanum ostruthium (L.) W.D.J. Koch (Apiaceae) is a perennial herb native to alpine regions that is renowned in traditional medicine. This study provided a pharmacognostic evaluation, comparing the EOs obtained from its rhizomes and leaves (REO and LEO, respectively). A micromorphological analysis, which was carried out using fluorescence and scanning electron microscopy, revealed terpenoid-rich secretory ducts in both organs. The EOs were extracted by hydrodistillation and characterized by gas chromatography, coupled with flame ionization detection and mass spectrometry (GC-FID and GC-MS), revealing distinct chemical profiles. REO was dominated by monoterpenes (80.08%), especially D-limonene (29.13%), sabinene (19.77%), and α-phellandrene (12.02%), while LEO was sesquiterpene-rich (81.15%), with β-caryophyllene (21.78%), β-selinene (14.09%), and germacrene D (10.43%) as the major compounds. The in vitro assays demonstrated that both EOs exhibit significant antioxidant and anti-inflammatory activities, with LEO consistently outperforming REO across all tests. However, neither EO showed antimicrobial effects against common bacterial or fungal strains. This may have been due to the absence of polar antimicrobial constituents, such as coumarins, which are poorly recovered by hydrodistillation. To fully exploit the therapeutic potential of P. ostruthium, especially its antimicrobial properties, future studies should aim to develop integrated formulations combining volatile and non-volatile fractions, preserving the complete plant complex and broadening bioactivity.